Fiscal reform in Mexico - Sobarzo, Horacio (Estudios Económicos de El Colegio de México, 2004)
This document reports the results of an applied general equilibrium model built to evaluate the fiscal reform initiative of the Mexican government. Taking public revenues as endogenous and tax rates as exogenous variables, the model incorporates in an explicit manner both the tax structure of the Mexican economy and the oil exporting sector as an important source of government revenue. The results confirm that, to a great extent, the so-called fiscal problem in Mexico stems from a low degree of tax compliance, and no so much from variations of the international price of oil. A fiscal reform focusing on the widening of the tax base through a non-zero VAT on food and medicines, does not appear to have strong income distribution impacts. To the extent that developing countries may find strong obstacles to increase tax revenues from taxation of income, these results are important.